Texture, reading and meaning: notions, nebulae and the numinous - Jensen, Justin M., author; Yust, Dave, 1939-, advisor; Sullivan, Patrice M., advisor; Chong, Edwin Kah Pin, committee member; Simons, Stephen R., committee member (Colorado State University. Libraries, 2007)
The thesis is commenced by a development of a theory about art that encompasses what is referred to as the texture, the reading and the saying. The first refers to that of which the art is composed, the second refers to the referential aspect, and the third refers to the intended meaning. Each of these aspects has a value that is independent yet supported by the previous. This is the basis for my critical development in art. Within the texture level I discuss how the painting process is clarified as a push and pull between texture and render. The latter part of the thesis develops the key points for the saying aspect of my work. Sacred Time and real time is an idea used in mythological that clarifies the otherworldy nature of myth. This idea is carried into my thesis research and is developed by the dichotomy characterized as the numinous and the Weltschmerz. The numinous can be defined as sublime, or the feeling of the presence of the holy. Weltschmerz can be regarded as the feeling of the wrongness of the world. These two feelings come together in what C. S. Lewis describes as Joy, which is referenced in the appendix. The primary theme that I use to explore this feeling is the inclusion of deep-space celestial objects into terrestrial landscapes. This carries the symbolism of the mystery of the universe of that which is far seeming like it ought to be closer. It is the evocation of a moment of sacred time within real time. My intention in the sky-scape paintings is summarized in trying to create a place that is transcendent of time where we realize a truth about our own world. It is a myth that focuses a truth into clarity.
Keywords: Holy, The, in art